Effective Language Learning (Eurasian Research Bulletin, 2022)
This article is dedicated to get acquainted with the term “effective language learning”, learners’ styles and features as well . Additionally , the article concentrates on scientific books, researches and its results which provide learners with opportunities to gain more understanding